2009
DOI: 10.1097/jom.0b013e3181ad49c8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma in World Trade Center Responders: A Case Series

Abstract: In this case series, we observe an unusual number of MM cases in WTC responders under 45 years. This finding underscores the importance of maintaining surveillance for cancer and other emerging diseases in this highly exposed population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 28 publications
4
45
0
Order By: Relevance
“…By studying cancer incidence rate among workers of rescue, recovery, reconstruction, and volunteers who were exposed to the heavy dust cloud at Ground Zero and registered in the New York/New Jersey consortium of the WTC Medical Monitoring and Treatment Program (MMTP), Moline et al . noted 8 cases of MM, four of them were younger than 45 years4. This observation was supported by another longitudinal study of 55,778 New York State residents, which revealed excess incidence in responders for MM5.…”
supporting
confidence: 53%
See 3 more Smart Citations
“…By studying cancer incidence rate among workers of rescue, recovery, reconstruction, and volunteers who were exposed to the heavy dust cloud at Ground Zero and registered in the New York/New Jersey consortium of the WTC Medical Monitoring and Treatment Program (MMTP), Moline et al . noted 8 cases of MM, four of them were younger than 45 years4. This observation was supported by another longitudinal study of 55,778 New York State residents, which revealed excess incidence in responders for MM5.…”
supporting
confidence: 53%
“…1A). Since concerns had been arisen about the potential for increased risk of MM among WTC responders45, we also investigated the capability of WTC dust on the induction of mdig in normal B cells using a B cell line C5B7. Similar to what we observed in BEAS-2B cells, we noted a dose-dependent induction of mdig protein and mRNA by WTC dust in C5B7 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, only one study investigating WTC-related cancer has described eight cases of multiple myeloma in WTC responders, but uncertainty related to the definition of exposure and the exact population at risk limit the generalisability of its conclusions. 2 Our study is a preliminary effort to examine incidence of cancers occurring within the first 7 years after 9/11 in a cohort of nearly 10 000 male firefighters with known health information before 9/11 and minimal loss to follow-up.…”
Section: Introductionmentioning
confidence: 99%